2012
DOI: 10.1111/j.1464-5491.2012.03637.x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy screening: perspectives of people with diabetes, screening intervals and costs of attending screening

Abstract: Our study suggests that people with diabetes undergoing diabetic retinopathy screening would accept a greater screening interval, provided that adequate clinical evidence and medical reassurance were given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…42,43 A comprehensive primary care model has been suggested to enhance the effectiveness of primary care providers and degree of collaboration between primary care providers and eye care services providers. 44 Our finding that known clinical risk factors such as sex, age, and duration of diabetes are associated with visual impairment is in line with other epidemiologic studies, [45][46][47][48][49][50] which indirectly validates the other conclusions of the study.…”
Section: Resultsmentioning
confidence: 99%
“…42,43 A comprehensive primary care model has been suggested to enhance the effectiveness of primary care providers and degree of collaboration between primary care providers and eye care services providers. 44 Our finding that known clinical risk factors such as sex, age, and duration of diabetes are associated with visual impairment is in line with other epidemiologic studies, [45][46][47][48][49][50] which indirectly validates the other conclusions of the study.…”
Section: Resultsmentioning
confidence: 99%
“…In 2012, Yeo conducted two studies [ 53 , 54 ]: The first [ 53 ] was based on 1550 questionnaires distributed at DR clinics in Wales, with 600 complete responses analysed. Eighty-five percent ( n = 507) felt that they should have their eyes screened every year.…”
Section: Resultsmentioning
confidence: 99%
“…There is a large gap in knowledge and research on how this will affect individual patient behaviors and attendance for screening programmes. Work by Yeo [ 53 , 54 ] has suggested that respondents would accept screening at 2- or 3-year intervals if medical evidence showed that it was safe and as long as preferences for other attributes of service provision (ability of screening to detect other changes, explanation of results and travel time) were made available. However, there is no current evidence of patient’s behavior in these circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…The NSC has specified the need for stakeholder and service user involvement, but the acceptability of stratified screening has not yet been evaluated. The limited currently available evidence suggests that extended intervals may prove not to be acceptable, and may require a more complete evidence base .…”
Section: Challenges Of Transitionmentioning
confidence: 99%